Linaria semialata and L. amethystea subsp. aedoi, two new taxa of L. sect. Supinae (Plantaginaceae) from Southeastern Iberian Peninsula - Jiménez, Juan F.; López, David; Vera, Juan B.; Güemes, Jaime; Sánchez-Gómez, Pedro (Phytotaxa, 2020)
Two new taxa of the genus Linaria are described, illustrated and compared, through a morphometric analysis, to morphologically similar species from L. sect. Supinae: L. amethystea, L. diffusa, L. intricata, and L. orbensis. A Principal Component Analysis and Linear Discriminant Analysis were carried out in order to find out which morphological characters were the most important to discriminate these species. Morphometric analyses revealed that discrimination of species were more related to their particular morphological character combinations than to a private character. Two taxa are described as new to science, by providing a detailed description, illustrations, scanning-electron micrographs and an identification key.